2020
DOI: 10.1016/j.jaridenv.2020.104284
|View full text |Cite
|
Sign up to set email alerts
|

Seed dispersal potential of jackals and foxes in semi-arid habitats of South Africa

Abstract: We determined the consumption of fruits and estimated potential seed dispersal of a canid community in semi-arid ecosystems of South Africa by comparing diets, defecation sites, densities and potential seed shadows of cape foxes (Vulpes chama), bat-eared foxes (Otocyon megalotis) and black-backed jackals (Canis mesomelas) on Benfontein and Rooipoort nature reserves. On Benfontein, all canid species consumed the fruit of Diospyros lycioides throughout the year. Jackals, but neither fox species, consumed relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 69 publications
(120 reference statements)
1
4
0
Order By: Relevance
“…This is consistent with a study by Kamler et al. (2020) in a different region of southern Africa which showed that fruit consumption by black‐backed jackals was higher than that by cape foxes. It is possible that carnivores are generally important for dispersing seeds of African cucurbits as Mills and Mills (1978) noted that brown hyaenas in the Kalahari frequently consume the cucurbits Acanthsicyos naudinianus (gemsbok cucumber) and Citrillus lanatus (tsama melon).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with a study by Kamler et al. (2020) in a different region of southern Africa which showed that fruit consumption by black‐backed jackals was higher than that by cape foxes. It is possible that carnivores are generally important for dispersing seeds of African cucurbits as Mills and Mills (1978) noted that brown hyaenas in the Kalahari frequently consume the cucurbits Acanthsicyos naudinianus (gemsbok cucumber) and Citrillus lanatus (tsama melon).…”
Section: Discussionsupporting
confidence: 93%
“…Carnivore species implicated in seed dispersal include coyotes ( Canis latrans ) in north temperate regions (Willson, 1993), Asiatic black bears ( Ursus thibetanus ) in cool temperate deciduous forests (Koike et al., 2008), red and corsac foxes ( Vulpes vulpes and Vulpes Corsac , respectively) in the Mediterranean (Juan et al., 2006; Rosalino, Rosa, & Santos‐Reis, 2010) and in Mongolia (Murdoch et al., 2009). In semi‐arid areas of South Africa, cape foxes ( Vulpes chama ), bat‐eared foxes ( Otocyon megalotis ) and black‐backed jackals ( Canis mesomelas ) have been suggested to have potential as seed dispersers (Kamler et al., 2020). However, the potential of carnivores as seed dispersers in hyper‐arid desert environments has been largely overlooked.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scats of jackals were distinguished from other species based on size, placement, and DNA analysis of selected scats. Jackals typically defecate on elevated objects, such as small shrubs and tufts of grass, that line trails or dirt tracks ( Macdonald 1979 ; Kamler et al 2020a ), rather than directly on the paths themselves. We took a random sample of 10 putative jackal scats collected from shrubs and tufts of grass, and sent them to the Sackler Institute for Comparative Genomics, American Museum of Natural History (New York), who confirmed that the scats were from jackals based on mitochondrial DNA analysis as described by Caragiulo et al (2014) .…”
Section: Methodsmentioning
confidence: 99%
“…Black-backed jackals have the potential to be effective seed-dispersal agents when soft mast, a supplementary resource, is included in individual diets (Do et al 2009;Kamler et al 2020). While it has not yet been evaluated whether individual rank within the dominance hierarchy affects soft mast consumption in this species, it has been shown that rank affects individual space use such that subordinate individuals move farther distances and are more likely to go on extraterritorial forays (Kamler et al 2019), likely increasing the distance that seeds are moved and the diversity of habitats where seeds arrive.…”
Section: Black-backed Jackal (Canis Mesomelas)mentioning
confidence: 99%